Unintentional injuries and associated factors among adolescents - Bordalo,Diana (2020)
Abstract Introduction: Unintentional injuries are an important cause of death in adolescents, as well as a major cause of ill health. This age group is prone to unintentional injuries due to their specific biological, psychological, and social characteristics. To prevent these injuries, it is crucial to understand their prevalence and associated factors. The aim of this study was to identify and characterize unintentional injuries in adolescents and their potential impact on health and life. Material and Methods: Prospective, observational, two-center study over one year based on a survey of adolescents admitted to the Emergency Department due to unintentional injuries. Results: The study included 1054 adolescents (840 from Center A and 214 from Center B), mostly male (58.2%), 51.6% of which in early adolescence (10 to 13 years old) and only 11.2% in late adolescence (17 to 18 years old). Alchool or drug use were reported by 2.3% of participants. Main reported injuries included traumatic injuries (mainly during sports), accidental falls (mainly at school), and road traffic accidents (being run over by a car as the most frequent). Acidental falls and traumatic injuries were more common in early adolescence, whereas burns, road traffic accidents, and intoxications were more frequent in middle adolescence. Low frequency of personal protection equipment use (31.3%) was reported by bycicle riders. School absence was reported in 31% of cases, mainly associated with traumatic injuries (49.8%) and falls (40.1%). Conclusion: Most reported unintentional injuries had preventable causes and their prevalence was developmental stage-dependent. These results provide additional data for implementation of preventive measures according to developmental adolescence stages.